Об одной задаче граничного управления колебаниями струны - Резникова, С. А. (ХНУРЭ, 2016)
В работе рассмотрена задача оптимального управления процессом колебаний струны за счет подбора управляющих воздействий на концах этой струны. Целью управления является достижение такого положения струны, которое в конечный момент времени будет наиболее близко к заданному. Different mathematical models in many cases reduce to the differential equations of the hyperbolic type. These equations are most frequently found in physical problems concerned with processes of vibration, e.g. the problem of the vibration of a string, membrane, gas, electromagnetic oscillation etc. Characteristic property of the processes, describable by this kind of equations, is finite velocity of their propagation. The purpose of the paper is to investigate the problem of vibration processes, which defined by the hyperbolic equation, and optimal control of these processes.
Keywords: Неоднородное уравнение колебаний струны; Оптимальное управление; Краевые и начальные условия; Функционал качества; Метод Фурье; The one-dimensional wave equation; The optimal control; Boundary and initial conditions; The quality functional; The Fourier method